ATIM-23. ANTI-CD27 AGONIST ANTIBODY VARLILUMAB IN COMBINATION WITH NIVOLUMAB FOR RECURRENT GLIOBLASTOMA (rGBM): PHASE 2 CLINICAL TRIAL RESULTS. (5th November 2018) - Reardon, David; Kaley, Thomas; Iwamoto, Fabio; Baehring, Joachim; Subramaniam, Deepa; Rawls, Tracey; He, Yi; Keler, Tibor; Yellin, Michael
Abstract: CD27 is a key immunostimulatory molecule that enhances T cell survival, activation and effector function, as well as proliferation and cytotoxic activity of NK cells. Preclinical studies demonstrate synergistic activity of PD-(L)1 blockade and varlilumab, an anti-CD27 agonist monoclonal antibody. In an open-label Phase 2 study (NCT02335918), patients with bevacizumab-naïve, rGBM following first line chemoradiation received varlilumab (3 mg/kg, up to 16 doses) and nivolumab (240 mg) Q2W. Objectives were to determine preliminary antitumor activity based on 12-month survival rate (OS12; primary), objective response rate (ORR; iRANO), progression-free survival (PFS), as well as tolerability. 22 patients were enrolled: 23% methylated MGMT (mMGMT), 68% unmethylated MGMT (uMGMT), 9% unknown; median age 58 years; 68% male; 36% ECOG performance status 0, 64% ECOG 1; 4/18 (22%) PD-L1+ tumor. Safety profile was consistent with that of each agent alone and generally grade 1–2, without dose-limiting toxicity or drug-related deaths. The most common toxicities were lymphopenia, pruritus, headache, and rash. Two patients experienced treatment-related serious events (grade 2 gait disturbance, headache and personality changes; and grade 4 thrombocytopenia). OS12 was 38.5% (95% CI; 18.6, 58.2) overall and 43.6% (95% CI; 18.2–66.7) for the uMGMT subgroup. Median OS (months) was 9.7 (95% CI; 6.7–14.8) overall and 11.3 (95% CI; 5.3, -) for the uMGMT subgroup. Eight patients (6 uMGMT, 1 mMGMT, 1 unknown) survived 12 months (range: 13.7 - 23+). Two patients (9%; both uMGMT) experienced Partial Responses (63% and 92% shrinkage) continuing at 19 and 16 months. Nine patients experienced stable disease, including 5 for 6 months (range: 7.3 - 20.3). Varlilumab with nivolumab was generally well tolerated in patients with rGBM and achieved durable therapeutic benefit in a subset of patients, although overall ORR and OS12 were similar to historical nivolumab monotherapy data. Outcome among uMGMT rGBM patients may be encouraging.